2017
DOI: 10.14393/bj-v33n3-37165
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and selection in tomato genotypes under water stress induced by mannitol

Abstract: ABSTRACT:The tomato crop adapts to different climatic conditions. However, the water stress, which is a relevant factor in the tomato cropping, can affect the productivity. This experiment aimed to estimate the genetic variability, after two backcrosses, and select tomato genotypes that are tolerant to water stress induced by mannitol. The advance of the generations was done on the field and the water stress test was done in laboratory atmosphere, in a completely randomized design with four replications. 17 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…pennellii LA716 is another valuable genetic source conferring tolerance to various biotic and abiotic stresses. For example, it is tolerant to abiotic stresses such as salt (Frary et al, 2010;Li et al, 2010) and drought (Borba et al, 2017), Moreover, LA716 showed high resistance to the obligate parasitic plants (Orobanche aegyptiaca) (El-Halmouch et al, 2006) and Phelipanche aegyptiaca (Bai et al, 2020). While previous work indicated that LA716 has resistance to different biotic stresses such as whitefly (Bemisia tabaci) (Baldin et al, 2005;Oriani and Vendramim, 2010); tomato miner, Tuta absoluta (Bitew, 2018); a bacterial spot disease caused by Xanthomonas campestris pv.…”
Section: Resultsmentioning
confidence: 99%
“…pennellii LA716 is another valuable genetic source conferring tolerance to various biotic and abiotic stresses. For example, it is tolerant to abiotic stresses such as salt (Frary et al, 2010;Li et al, 2010) and drought (Borba et al, 2017), Moreover, LA716 showed high resistance to the obligate parasitic plants (Orobanche aegyptiaca) (El-Halmouch et al, 2006) and Phelipanche aegyptiaca (Bai et al, 2020). While previous work indicated that LA716 has resistance to different biotic stresses such as whitefly (Bemisia tabaci) (Baldin et al, 2005;Oriani and Vendramim, 2010); tomato miner, Tuta absoluta (Bitew, 2018); a bacterial spot disease caused by Xanthomonas campestris pv.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that photosynthesis is the driving force for plant growth and that low water potentials reduce seedling growth by impairing cell expansion and division and photosynthesis (Borba et al, 2017; Flexas & Carriquí, 2020), it was expected that the genotypes with better water balance had also higher biomass production. However, some of the progenies with higher biomass production did not show higher A, wilt resistance and RWC, such as the UZTI‐14, UZTI‐55, UZTM‐65 and UZTM‐50, indicating that these progenies respond differentially to drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, performance per se is one of the main standards applied in the selection of superior tomato genotypes. For that matter, the univariate analysis using the Scott-Knott test of means (Scott and Knott, 1974) has been widely used by several authors (Araújo et al, 2016;Borba et al, 2017;Finzi et al, 2017;Maciel et al, 2018;Peixoto et al, 2018). Nevertheless, it is known that this type of selection can be inefficient, because it leads to a superior genotype in no more than one characteristic.…”
Section: Introductionmentioning
confidence: 99%